Cohort retrospective study: the neutrophil to lymphocyte ratio as an independent predictor of outcomes at the presentation of the multi-trauma patient - Soulaiman Elias Soulaiman (International Journal of Emergency Medicine, 2020)
Abstract Background Although the association of neutrophil to lymphocyte ratio (NLR) with mortality in trauma patients has recently been shown, there is a paucity of research on the association with other outcomes. Recent studies suggest that the NLR has a predictive value of mortality in trauma patients during various times of admission. This study aimed to determine the prognostic impact of NLR at the presentation in critically ill trauma patients. Methods A retrospective cohort study of adult trauma patients between July 2017 and November 2017 in Tishreen Hospital. All patients who had arrived at the emergency department with multi-trauma injury within the age category (14–80 years) were included in this analysis. The prophetical capability of NLR on mortality was assessed by the receiver operative characteristics (ROC) curve. To identify the impact of the NLR on survival, a separate log-rank test was used. Multivariable Cox proportional hazard modeling was used to identify independent predictors of mortality. Results Throughout the time of the study, 566 patients met the inclusion criteria. Of these, 98.8% were male, 75.8% sustained penetrating trauma, and median age [IQR25–IQR75] was 26 [23–32]. Ninety-seven patients (17.1%) had major trauma, with an Injury Severity Score (ISS) ≥ 15. Using the ROC curve analyses hospitalization day 1, optimal NLR cutoff values of 4.00 were calculated by maximizing the Youden index. Kaplan-Meier curves revealed an NLR greater than or equal to these cutoff values as a marker for increased in-hospital mortality (p = 0.020, log-rank test). The Cox regression model demonstrated significant collinearity among the predictive variables (all VIF results < 2). Only ISS > 15 has a significant statistical relation with elevated NLR on day 1 (p = 0.010). Conclusions Elevated NLR on day 1 has high predictive power for overall survival during the first 30 days after trauma, but it was not independent of other factors.